Parental Involvement and Students Academic Outcome: Exploring the Mediating Role of Academic Motivation - Sardar Nasir Sohail Khan; Naseem Ullah; Sofia Saba (The Sky)
The research is aimed to determine the influence of mediating variable academic motivation in relationship between parental involvement and academic outcomes (dropout/pass) partially and complementarily among intermediate 1st year students. Additionally, significant differences were explored in independent variable of parental involvement and mediating variable of academic motivation between passing and dropout students. The study included randomly selected 350 intermediate students; 223 passed the part-I annual examination, whereas 127 did not. Data on parental involvement, academic motivation, and academic outcomes were collected and analyzed using mediation and comparative (inferential) statistical methods. The hypotheses were supported by the results: the association between parental involvement and academic outcomes was partially mediated by academic motivation. Furthermore, complementary mediation was observed, indicating that academic motivation enhances the effect of parental involvement on academic outcomes. Pass students exhibited significantly higher levels of parental involvement and academic motivation compared to dropout students. The findings suggest that both parental involvement and academic motivation play crucial roles in determining academic outcomes among intermediate 1st year students. Enhancing parental involvement can positively influence academic motivation, thereby improving academic success and reducing dropout rates. Based on the results, it is recommended to promote strategies that increase parental involvement in students’ academic lives. Schools and policymakers should also focus on fostering academic motivation among students, particularly those at risk of dropping out, to enhance their academic performance and retention.